DIABETES INSIPIDUS MASQUERADING PITUITARY ADENOMA - Aini, EW Nur; Fadilah, M Aimi; Faradilla, WMH Sharifah; Zaherah, MS Fatimah; Aisyah, Z Nur; Hazriq, A Mohd; Rohana, AG (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Central diabetes insipidus (CDI) is rare with a prevalence of 1 in 25000, most commonly due to pituitary surgery or trauma (50%) and hypophysitis (15%). We reported a rare case of CDI masquerading as a pituitary adenoma. RESULTS A 54-year-old woman with diabetes mellitus presented with generalised seizure. She had polyuria >3L/day and polydipsia for 6 months. She had no menses since age 45, and no history of postpartum complications. Galactorrhoea, increased weight/shoe size, changes in facial appearance, headache, blurring of vision, postural dizziness and hypothyroid symptoms were absent. She was obese (body mass index 49 kg/m2), with BP 124/62, HR 62, and no postural hypotension. There were no abdominal striae, proximal myopathy, frontal bossing, spade-like hands nor bitemporal hemianopia. She had hypernatraemia (152mmol/L), high serum osmolality (320 mOsm/kg) and low urine osmolality (80 mOsm/kg). Urine osmolality increased to 340 mOsm/kg after desmopressin. She had central hypocortisolism (cortisol 14 nmol/L, ACTH 22 pg/ mL), central hypothyroidism (fT4 7.1 pmol/L, TSH 0.58 mIU/L), hyperprolactinaemia (3387 mIU/L, 3974 mIU/L post-dilution) and secondary hypogonadism (oestradiol 232 pmol/L, LH <0.1 IU/L, FSH 1.4 IU/L). Random morning GH was 0.1 ng/mL. IGF-1 was not sent as there was no clinical suspicion of acromegaly. Pituitary MRI showed a well-defined enhancing sellar mass with suprasellar extension measuring 1.3 cm x 1.4 cm x 1.6 cm, suggestive of a pituitary macroadenoma with central necrosis and loss of posterior pituitary brightness on plain T1 MRI. The adenoma was removed via transsphenoidal surgery, and histopathology showed pituitary adenoma which stained positive for GH and prolactin. There was no evidence of hypophysitis on histology. CONCLUSION Pituitary adenomas rarely present as CDI. In few reports, all had concurrent hypophysitis on histopathology (1-4). Our patient had biochemically confirmed CDI and radiologic findings suggestive of adenoma and hypophysitis. However, histopathology only showed pituitary adenoma with no evidence of hypophysitis.